MODEL STRUKTURAL KEPATUHAN WAJIB PAJAK UMKM BERBASIS MANAJEMEN PEMASARAN LAYANAN DAN DIGITALISASI PERPAJAKAN - M. Gunawan Setyadi; M. Hasan Ma'ruf; Abdullah Zailani (ITB AAS Indonesia Surakarta, 2026)
This study examines the effects of service marketing management and tax digitalization on taxpayer compliance through taxpayer experience, satisfaction, and trust. An explanatory quantitative approach and a cross-sectional survey were employed involving 275 individual taxpayers who owned or managed micro, small, and medium enterprises in Greater Surakarta. Data were analyzed using Partial Least Squares Structural Equation Modeling. Service marketing management and tax digitalization positively affected taxpayer experience. Experience positively influenced satisfaction, satisfaction enhanced trust, and trust improved taxpayer compliance. Taxpayer experience specifically mediated the effects of service marketing management and digitalization on compliance. However, serial mediation through experience and satisfaction without trust was not significant. In contrast, the complete experience–satisfaction–trust chain significantly mediated both exogenous relationships. The findings indicate that satisfaction alone is insufficient to translate service and digitalization into compliance; institutional trust is the decisive relational mechanism. The model explained 19.1% of the variance in taxpayer compliance. The study highlights the need to integrate service orientation, user experience, digital support, satisfaction, and trust-building in strategies to strengthen voluntary tax compliance. Keywords: PLS-SEM; service marketing management; tax digitalization; taxpayer compliance;